2016
DOI: 10.1080/07370652.2016.1194499
|View full text |Cite
|
Sign up to set email alerts
|

An Acid-Catalyzed Cascade Synthesis of Oxaazatetracyclo [5.5.0.03,11.05,9]dodecane Derivatives

Abstract: A condensation between mesylamide and glyoxal under highly acidic conditions was studied. A series of new compounds whose structures contain a moiety of oxaazatetracyclo[5.5.0.0 3,11 .0 5,9 ]dodecane were synthesized. The synthesis processes were optimized and main factors affecting the assembling of cage products were revealed. Assumptions are made regarding the formation mechanism of these chemical entities. For the first time, compounds have been obtained that include moieties of 2,6,8-trioxa-4,10,12-triaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We have previously explored the condensation between substituted sulfonamides (methanesulfonamide, benzenesulfonamide, 4-dimethylaminobenzenesulfonamide or isopropylsulfonamide) and glyoxal, whereby a series of new oxaazaisowurtzitane derivatives were obtained, some polyheterocyclic caged systems were discovered and new condensation regularities were established [ 62 , 63 , 64 ]. More specifically, the increased basicity of the amido group in the sulfonamide molecule was found to facilitate the incorporation of aza groups into the oxaazaisowurtzitane cage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously explored the condensation between substituted sulfonamides (methanesulfonamide, benzenesulfonamide, 4-dimethylaminobenzenesulfonamide or isopropylsulfonamide) and glyoxal, whereby a series of new oxaazaisowurtzitane derivatives were obtained, some polyheterocyclic caged systems were discovered and new condensation regularities were established [ 62 , 63 , 64 ]. More specifically, the increased basicity of the amido group in the sulfonamide molecule was found to facilitate the incorporation of aza groups into the oxaazaisowurtzitane cage.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research focused on upgrading the existing synthetic technologies for CL-20 and on finding alternative methods for obtaining the same has been pursued, dating back decades. The most promising direction is to develop a synthetic method for hexaazaisowurtzitane derivatives by direct condensation, which are nitratable to CL-20 [ 16 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…While selecting amides, we took into account the basicity of the reagents and the ease of N-nitration of the condensation products, except for mesyl amide that is highly resistant to acidic medium and capable of generating polyheterocyclic cage compounds. The basicity of amides and the tendency of their condensation products toward N-nitration depends on the value of the partially negative charge on the amide nitrogen atom. This charge is due to the inductive effect of the substituent and increases in the row: CH 3 SO 2 NH 2 < HCONH 2 < CH 3 CONH 2 < (CH 3 ) 2 CHCONH 2 < CH 3 CH 2 CONH 2 < (CH 3 ) 3 CCONH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…1 The density of nitramines increases as the molecular rigidity rises. 2 The most common nitramine bearing a strained polyheterocyclic cage is 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12hexaazatetracyclo[5.5.0.0 3,11 .0 5,9 ]dodecane (CL-20, hexanitrohexaazaisowurtzitane, HNIW) (Figure 1). This chemical entity is one of the most powerful explosives domesticated by humankind (ρ = 2.044 g/cm 3 , V 0 D = 9.36 (ε) km/s).…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1] It has more recently been found that compounds similar to oxaazaisowurtzitane derivatives can be synthesized by condensation between sulfonamides and glyoxal. [16,17] The development of synthetic methods for high-energy compounds bearing strained moieties and capable of being further transformed into more complex high-energy…”
Section: Introductionmentioning
confidence: 99%